Downregulation of MicroRNA-222 Reduces Insulin Resistance in Rats with PCOS by Inhibiting Activation of the MAPK/ERK Pathway via Pten - Hong Ye; Xiu-Juan Liu; Yan Hui; Yang-Huan Liang; Cai-Hong Li; Qiong Wan (Elsevier, 2020)
Polycystic ovary syndrome (PCOS), characterized by the dysfunction of endocrine metabolism, is a common disease among women. Insulin (INS) resistance (IR) is considered as an obstruction to effective PCOS treatment. Here, we aimed to explore the mechanism by which microRNA-222 (miR-222) affects IR in PCOS via Pten. Quantitative reverse transcription-polymerase chain reaction and western blot assays indicated that miR-222 expression was higher in the peripheral blood of PCOS patients with IR than in PCOS patients without IR, while Pten expression was lower. Further mechanistic analysis identified Pten as a target gene of miR-222. Moreover, PCOS rat models were established through the administration of dehydroepiandrosterone and were subsequently treated with miR-222 agomir, miR-222 antagomir, or Pten overexpression plasmid. The inhibition of miR-222 improved ovarian morphology, enhanced the production of serum sex hormones (follicle-stimulating hormone [FSH], luteotropic hormone [LH], estradiol 2 [E2], prolactin [PRL], and testosterone [T]), increased the levels of glucose metabolism indicators (homeostasis model of assessment for IR [HOMA-IR], blood glucose [BG]120min, and INS120min), and reduced the production of progesterone in the PCOS rats. Notably, miR-222 downregulation resulted in the inactivation of the mitogen-activated protein kinase (MAPK)/ERK pathway by upregulating Pten. Collectively, miR-222 inhibition might reduce IR in PCOS by inactivating the MAPK/ERK pathway and elevating Pten expression, which indicates miR-222 as a promising target for PCOS treatment.